Adjuvant radiotherapy for the treatment of stage IV rectal cancer after curative resection: A propensity score-matched analysis and meta-analysis. Issue 47 (November 2016) - Kim, Min Jung; Kim, Sang Jin; Park, Sung-Chan; Kim, Dae Yong; Park, Ji Won; Ryoo, Seung-Bum; Jeong, Seung-Yong; Park, Kyu Joo; Oh, Heung Kwon; Kim, Duck-Woo; Kang, Sung-Bum; Joo, Jung Nam; et al.
Abstract : Abstract: The role of pelvic radiotherapy (RT) in stage IV rectal cancer with total mesorectal excision (TME) has not been defined. We evaluated the impact of RT on oncologic outcomes among patients with stage IV rectal cancer who underwent TME and performed a meta-analysis of published studies. The records of stage IV rectal cancer patients who underwent TME between August 2001 and December 2011 were reviewed. Patients who received pelvic RT (RT group) and those who did not (non-RT group) were matched using a propensity score. Oncologic outcomes were compared between the groups. A systematic literature search and meta-analysis was conducted. One hundred seventy-six patients were matched with propensity score matching, resulting in 39 patients in each group. The local recurrence-free survival (LRFS) of the RT group was significantly higher than that of the non-RT group (2-year LRFS: 100% vs 83.6%, respectively, P  = 0.038). The overall survival, disease-free survival, and systemic recurrence were not significantly different between the groups. In the meta-analysis, the RT group had a reduced risk for loco-regional recurrence than the non-RT group (RR: 0.48, 95% confidence interval: 0.29–0.79). Pelvic RT might have benefits for loco-regional control in patients with stage IV rectal cancer who undergo TME. Abstract : Supplemental Digital Content is available in the text